Changes and Existence of Rivers in Cirebon City 1900-1942 - Faisal Arif; Anwar Sanusi; Didin Nurul Rosidin; Aditia Muara Padiatra (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2020)
In the Hindu-Buddhist period until the VOC, the role of the river was very important, because the river was the main highway that was easy and needed by the people of Cirebon as a means of transportation to connect the coastal area (Port) with the interior (hinterland). But during the Dutch East Indies, the existence of rivers in the city of Cirebon has been changed. As the underlying factors, the change in the existence of a river is: firstly, Along with the time and technology development also the increasing of goods and services needs that continue to the needs of exploitation of colony, as well as for make efficient the distribution of goods and services, which then continues to the Government of the Indies-Netherland make the change from river transportation modes to many modes of land transportation development like highways and trains, secondly, unhealthy river ecological conditions also influence, so many people are often affected by disease outbreaks due to unhealthy river conditions and when the rainy season comes, the river overflows and floods people's homes (flooding). These factors are the background of the Indies-Netherland government to make a change to the existence of rivers in the city of Cirebon, such as dredging the Old River